Implementasi Profil Pelajar Pancasila Dimensi Bernalar Kritis Dalam Pembelajaran Matematika Kelas IV di Sekolah Dasar - Nurfaida, Siti; Sumardjoko, Bambang; Fuadi, Djalal (Jayapangus Press, 2025)
This study aims to describe how the implementation of the Pancasila Student Profile in the critical reasoning dimension in learning Mathematics grade IV at Inpres 12 Prafi Manokwari Elementary School. This research is a descriptive qualitative research. The subjects in this study are students and teachers of grade IV elementary school Inpres 12 Prafi Manokwari. The data collection technique uses observation, interviews, and documentation studies. The data analysis technique using Miles and Huberman includes four stages: 1) Data collection, 2) Data reduction, 3) Data presentation, and 4) Conclusion. The results of the study show that the application of critical reasoning has been applied by teachers and fourth-grade students. The application of the critical reasoning dimension has fulfilled all aspects, including: 1) Obtaining and processing information and ideas, 2) Analyzing and evaluating reasoning, and 3) Reflecting and evaluating one's own thoughts. Based on the results of the research, it can be concluded that the implementation of the Pancasila Student Profile with a critical reasoning dimension in learning Mathematics in grade IV of SD Inpres 12 Prafi Manokwari has been carried out very well.